Mimicry's palette: widespread use of conserved pigments in the aposematic signals of snakes. Issue 2 (March 2014) - Kikuchi, David W.; Seymoure, Brett M.; Pfennig, David W.
SUMMARY Mimicry, where one species resembles another species because of the selective benefits of sharing a common signal, is especially common in snakes. Snakes might be particularly prone to evolving mimicry if all species share some of the same proximate mechanisms that can be used to produce aposematic/mimetic signals. We evaluated this possibility by examining color pigments in 11 species of snakes from four different families, three species of which participate in a coral snake mimicry complex involving convergence in coloration. We found that all 11 species used combinations of two pteridine pigments and melanin in their coloration, regardless of whether or not they were mimics. Furthermore, the presence or absence of red pteridines was strongly correlated with the relative excitation of medium‐ and long‐wavelength photoreceptors in birds, thereby linking shared pigmentation to perception of those pigments by likely agents of selection. Thus, precise color mimicry might be relatively easy to evolve among snakes owing to symplesiomorphies in pigmentation.